2022
DOI: 10.1007/s41061-022-00387-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ and Operando Spectroscopies in Photocatalysis: Powerful Techniques for a Better Understanding of the Performance and the Reaction Mechanism

Abstract: In photocatalysis, a set of elemental steps are involved together at different time scales to govern the overall efficiency of the process. These steps are divided as follow: 1) photon absorption and excitation (in femtoseconds), 2) charge separation (femto-to picoseconds), 3) charge carrier diffusion/transport (nano-to microseconds), 4 & 5) reactant activation/conversion and mass transfer (micro-to milliseconds). The identification and quantification of these steps, using the appropriate tool/technique, can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 113 publications
0
17
0
Order By: Relevance
“…The response of the samples is characteristic of the dominant anatase phase, presenting the so-called green and red de-excitation peaks, roughly below and above ca. 500–525 nm. , PL changes through the series of catalysts correspond to a decrease of the overall intensity together with a shift of the maximum of the signal to higher wavelengths as a function of the noble metal content of the powder. A relevant point concerns the strong effect on the intensity of the signal exerted by the Pd noble metal.…”
Section: Resultsmentioning
confidence: 97%
“…The response of the samples is characteristic of the dominant anatase phase, presenting the so-called green and red de-excitation peaks, roughly below and above ca. 500–525 nm. , PL changes through the series of catalysts correspond to a decrease of the overall intensity together with a shift of the maximum of the signal to higher wavelengths as a function of the noble metal content of the powder. A relevant point concerns the strong effect on the intensity of the signal exerted by the Pd noble metal.…”
Section: Resultsmentioning
confidence: 97%
“…Raman and infrared (IR) spectroscopy techniques, can be used to distinguish structural information of molecules and further identify the key reaction intermediates and dynamic process on active sites. [140,141] For example, Wan et al [142] clearly revealed the degradation products and the corresponding structural evolution pathways of FePc molecule by in situ Raman spectroscopy. The degradation mechanism between molecular FePc and practical Fe-N-C catalysts was highly similar, and free radical attack was the main cause for the instability of FePc in acidic media.…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…Raman and infrared (IR) spectroscopy techniques, can be used to distinguish structural information of molecules and further identify the key reaction intermediates and dynamic process on active sites. [ 140,141 ] For example, Wan et al. [ 142 ] clearly revealed the degradation products and the corresponding structural evolution pathways of FePc molecule by in situ Raman spectroscopy.…”
Section: Identification Of Active Sites In Fe‐n‐c Catalystsmentioning
confidence: 99%
“…In efforts at better depicting the photocatalyst at work, in situ or operando measurements are in some cases feasible based on spectroscopic methods such as infrared spectroscopy (which allows CO bond rupture and the formation of CH and CC bonds to be followed). 2,3 Despite numerous studies on photoreduction of CO 2 , answers to many key questions remain unclear, even for the most commonly studied TiO 2 -based photocatalytic systems. Herein, we investigated the surface chemistry evolution and reaction mechanisms occurring on TiO 2 and associated Pt/TiO 2 (2 wt% Pt) in the photoreduction of CO 2 using real-time operando Fourier transform infrared (FTIR) spectroscopy.…”
mentioning
confidence: 99%